New approach to estimate coverage parameter in 3D FEM shot peening simulation. (2nd September 2017) - Pham, Trung Quang; Khun, Nay Win; Butler, David Lee
ABSTRACT: Shot peening is a surface cold working process used to enhance the fatigue life of metallic parts or members. Coverage is a major parameter of shot peening process, which is defined as the percentage of the sum of peened area over the total area on the surface of the specimen. In this paper, a new method is proposed to estimate the full coverage for simulation of the shot peening process. A dynamic plastic model of the shot peening process with the aid of Matlab TM code is also presented using the finite element method (FEM). The numerical results show that the coverage, shot velocity and radius significantly affect the residual stress distribution of the target material, AISI 4340 steel. In addition, a double-shot peening process is also studied in simulation to consider its effect on compressive residual stress distribution.